Pre-Retirement Employees' Entrepreneurial Intention: A Comprehensive Literature Review: A Comprehensive Literature Review - S.K. Halim; Ali, Hapzi (Jurnal Kewirausahaan dan Multi Talenta, 2025)
The global demographic shift toward an aging workforce presents both challenges and opportunities for organizational management and societal economic development. This comprehensive literature review examines the nascent yet increasingly critical domain of pre-retirement entrepreneurial intention, situated at the intersection of senior entrepreneurship, organizational support theory, and career transition literature. By synthesizing theoretical frameworks and empirical evidence from 2010 to 2025, this review establishes the conceptual foundations for understanding how retirement programs and perceived employer support influence entrepreneurial intentions among pre-retirement employees through the mediating role of personal attitude. Drawing primarily on the Theory of Planned Behaviour (Ajzen, 1991) and Career Construction Theory (Savickas, 2005, 2013), this review identifies critical research gaps, theoretical inconsistencies, and methodological limitations in existing scholarship while proposing directions for future investigation into this underexplored population's entrepreneurial potential.